Screening of sweet potato clones resistant to soil insects - Peixoto, José Ricardo; Santos, Luciana Cristina; Rodriges, Fabricio de Ávila; Juliatti, Fernando Cesar; Lyra, Jairo Roberto Mendonça (Pesquisa Agropecuaria Brasileira, 1999)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> A research was carried out with the objective of selecting commercial clones for weather conditions of the Triângulo Mineiro, Minas Gerais State, Brazil. Sixty of the clones evaluated were obtained by polycross and given by the Universidade Federal de Lavras, three were from the farmers of the municipalities of Araguari, Uberlândia and Machado, located in Minas Gerais State, and nine clones were used as standards (Brazlândia Branca, Brazlândia Rosada, Surpresa, Rio Doce, Morena Roxa, Coquinho, Arroba, Pira 1 and Clone 042). The experiment was installed in a spacing of 1.10 x 0.45 m, using a randomized block design, with 72 treatments, four replicates and 16 plants per plot. Among the evaluated clones, 32.8% showed high or moderate resistance to soil insects. The clone with the highest yield was the clone number 95041, which produced 28,048.96 kg/ha. The others, 95009, 95010, 95014, 95020, 95033, 95042 and 95057 were highly resistant to soil insects.